Goblet cell loss abrogates ocular surface immune tolerance - Ko, Byung Yi (JCI Insight, 2018)
Intestinal epithelial cells condition tolerogenic properties in DCs. Aqueous-deficient dry eye is associated with goblet cell (GC) loss and increased IFN-γ expression in the conjunctiva. We hypothesized that loss of GCs reduces tolerance-inducing properties of antigen presenting cells (APCs) in the conjunctiva and draining nodes. Mice lacking the SAM pointed domain containing ETS transcription factor (Spdef) that is required for GC differentiation had an increased frequency of macrophages in the conjunctiva and CD11b(+)CD11c(+) DCs in the conjunctiva and draining nodes, and these cells had greater IL-12 expression than WT mice. Conditioned media from cultured WT conjunctival GCs suppressed LPS-induced IL-12 production by conjunctival APCs. OVA antigen–specific OTII CD4(+) T cells primed by Spdef-KO draining lymph node APCs showed greater proliferation, lower frequency of Foxp3(+), increased frequency of IFN-γ(+) and IL-17(+) cells, and greater IFN-γ production than those primed by WT APCs. The immune tolerance to OVA antigen topically applied to the conjunctiva measured by cutaneous delayed type hypersensitivity (DTH) reaction, OVA-specific T cell proliferation, Foxp3 induction, and IFN-γ production observed in WT mice was lost in the Spdef-KO mice. We concluded that conjunctival GCs condition tolerogenic properties in APCs that suppress IL-12 production and Th1 polarization.